The Polar® OH1 Optical Heart Rate Sensor is Valid during Moderate-Vigorous Exercise - Schubert, Matthew M.; Clark, Amy; De La Rosa, Annie B. (Sports Medicine International Open, 2018)
Purpose Traditional heart-rate monitoring through the use of electrocardiograms or chest-worn heart rate sensors can be challenging in certain sports or in field settings. New technologies, such as photoplethysmography (PPG), have enabled heart-rate monitoring at alternate sites. However, to date, the accuracy and validity of various PPG sensors has not been examined in detail. The purpose of the present investigation was to determine the validity of an arm-worn PPG sensor during yoga sequences.Methods Fifteen college-aged men and women participated in a ~45 min power vinyasa yoga class. During the class, participants wore Polar® H7 chest straps and RCX3 receivers (criterion) and Polar® OH1 arm bands on their upper right arm (practical). Mean differences were compared via a paired t-test, heart rate during yoga using a time*device repeated measures ANOVA, and agreement assessed with Bland-Altman analysis.Results Mean heart rates during yoga were not different (mean difference=0.76, 95% CI: –0.54 to 2.06; p=0.229). Yoga created a main effect of time on heart rate (p<0.0001), but there was no difference between devices (p=0.86) or interaction (p=0.90). Mean bias±95% limits of agreement was 0.76±1.30 bpm, with a typical error of 2.42±1.49 bpm and a coefficient of variation of 1.8±1.5%.Conclusions Results of the present investigation revealed that the Polar® OH1 is a valid measure of heart rate during moderate-vigorous exercise. Future validation studies should consider other exercise modes and participant characteristics.
Keywords: Yoga; Agreement; Validation; Photoplethysmography